2003
DOI: 10.1063/1.1541151
|View full text |Cite
|
Sign up to set email alerts
|

Discrete quantum breathers: What do we know about them?

Abstract: The knowledge about discrete quantum breathers, accumulated during the last two decades, is reviewed. "Prehistory" of the problem is described and some important properties differentiating localized and extended vibrational modes are outlined. The state of art of our understanding of the principal features of the quantum discrete breathers is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 60 publications
(68 reference statements)
2
52
0
Order By: Relevance
“…In many cases quantum dynamics is important. Quantum breathers consist of superpositions of nearly degenerate many-quanta bound states, with very long times to tunnel from one lattice site to another [4,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Remarkably quantum breathers, though being extended states in a translationally invariant system, are characterized by exponentially localized weight functions, in full analogy to their classical counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases quantum dynamics is important. Quantum breathers consist of superpositions of nearly degenerate many-quanta bound states, with very long times to tunnel from one lattice site to another [4,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Remarkably quantum breathers, though being extended states in a translationally invariant system, are characterized by exponentially localized weight functions, in full analogy to their classical counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was suggested that Josephson junctions operating at higher energies may be used for experiments on quantum chaos [8,9,10]. Another phenomenon is the excitation of quantum breathers (QB) [11,12,13], which are nearly degenerate many-quanta bound states in anharmonic lattices. When such states are excited, the outcome is a spacially localized excitation with a very long time to tunnel from one lattice site to another.…”
mentioning
confidence: 99%
“…At present, because the occurrence of classical breathers is a relatively well understood phenomena, great attention has been paid to characterize their quantum equivalent, for which less detailed results are known [10]. In the quantum regime, the Bloch theorem applies due to the translational invariance of the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the corresponding eigenstates cannot localize the energy because they must share the symmetry of the translation operator which commutes with the lattice Hamiltonian. Nevertheless, the nonlinearity is responsible for the occurrence of specific states called multi-quanta bound states [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. A bound state corresponds to the trapping of several quanta over only a few neighbouring sites, with a resulting energy which is less than the energy of quanta lying far apart.…”
Section: Introductionmentioning
confidence: 99%